FREQUENCY OF VITAMIN D DEFICIENCY IN PATIENTS WITH BACKACHE IN GENERAL POPULATION - Adrees Shani; Basim Mubarik; Irshad Ahmad (Journal of University Medical & Dental College, 2017)
ABSTRACT:OBJECTIVE: To determine frequency of vitamin D deﬁciency in patients with backache in general population and to compare the result with international studies.STUDY DESIGN: Cross sectional Descriptive Case Series.PLACE AND DURATION: Outdoor patients of Medicine Department, Allied Hospital, Faisalabad, from 01-07-2016 to 31-12 -2016.MATERIALS AND METHODS: Adult patients of either gender with backache were included in the study. Patients of chronic renal failures, known rickets, osteomalacia and malabsorption were excluded. Non-probability consecutive sampling technique was used. After enrolment of patients according to criterion an informed consent was taken. Serum vitamin D 30ng/ml to 100ng/ml was taken as normal.RESULTS: Total number of patients were 100. Age ranged from 12-74 years (mean =36.72). Out of these 55% had suboptimal vitamin D levels (cut oﬀ value= 30ng/ml) of Which 67.27% were female and 32.73% were male having hypovitaminosis (P value = 0.946). Out of 100 patients 60% were below age 40 and 40% were above 40 and out of these 58.2% patients with vitamin D deﬁciency were below 40 years and 41.8% patients were above 40 years. (P = 0.682)CONCLUSION: Vitamin D deﬁciency is common in Pakistani population and needs to be considered in all patients with backache so that early supplementation of vitamin D can be done to improve health of our community.